Role of Nanoparticles for Wood Protection from Decaying Microorganisms and their Enzymes: A Review Study - Sulaiman A. Alsalamah; Mohammed Ibrahim Alghonaim; Mohamed A. Al Abboud (BioResources, 2025)
The growing need for sturdy lumber in many applications has made wood preservation more crucial. Nanoparticles (NPs) have been considered to improve the functionality of wood. This review article focuses on how NPs can be used to enhance the qualities of wood and wood-based products and provide them with anti-microbial protection. The ability of nano-based substances to permeate deeply into wood surfaces, which in turn causes a shift in their exterior chemistry, is the primary driver behind the nanotechnology application in lumber development. The microbial enzymes secreted by microbes is a major factor that can alter the structure of wood, especially during storage before use. This review illustrates various examples of microorganisms which secrete enzymes which impact wood structure through various mechanisms. The increased interface region created by the treatment serves as the reason for any prospective changes in the wood’s characteristics via NPs application. To a certain extent, the NPs change the original characteristics of wood, thus improving its qualities. There are challenges and limitations for using NPs in wood preservation. The potential effect of NPs on human health and the ecosystem should be considered using techniques such as life-cycle evaluations to avoid harmful consequences.